Toxic Positivity dalam Lagu Senyuman & Harapan: Perspektif Tasawuf - Azka Amalia; Dafa Alpahriza; Inry Aprilia; M. Zia Al-Haromain; Dadan Firdaus (Jurnal Ilmu Sosial dan Humaniora, 2026)
The phenomenon of toxic positivity is increasingly prevalent in modern society through various forms of communication and popular culture that encourage individuals to always maintain a positive attitude. This situation risks disregarding negative emotions, which are in fact a natural part of the human experience. This study aims to identify representations of toxic positivity in the lyrics of the song ‘Senyuman & Harapan’ by GAC and to analysethem through a Sufi perspective. The subject of this study is the lyrics of the song ‘Senyuman & Harapan’ by GAC. The study utilises the theory of toxic positivity by Whitney Goodman, as well as Al-Ghazali’s concepts of emotion regulation and patience, as the basis for its analysis. This study employs a qualitative approach using a descriptive-analytical method. Data were collected through a literature review and textual analysis of the song lyrics. The results indicate that the lyrics of the song ‘Senyuman & Harapan’ exhibit several indicators of toxic positivity, particularly the enforcement of a positive attitude and the suppression of negative emotions through the dominance of optimistic messages. From a Sufi perspective, the concept of patience does not reject negative emotions, but rather teaches the acceptance and management of emotions in a conscious manner through a spiritual approach. This study concludes that the message of optimism in the song can be understood as a form of positive motivation, but has the potential to lead to toxic positivity if it disregards the existence of negative emotions and the process of managing them.